Cultural-Perceptions of Russia and Russians in China Today - E. V. Senina; K. A. Poliakova (Концепт: философия, религия, культура, 2023)
The study of cultural-perception of countries and peoples’ has been gaining momentum in history, literary studies, ethnopsychology, journalism, imagology and other fields of scientific knowledge over the past decade. The cultrual-perception is constructed by ethnic, religious, political, ideological and artistic frames of perceptual consciousness. In connection with the development of Russian-Chinese relations, the topic of rethinking Oriental studies in line with the framework of the studies of philosophical and cultural problems is especially relevant today. The novelty of the research consists in updating the data already available in scientific publications on the culturalperception of Russia and Russians by the Chinese. This article examines the cultural-perception of Russia and Russians in China based on the results of polls conducted by the authors in 2021–2022. The poll contained open-ended questions concerning associations with Russia, symbols of the country, names of famous Russians, the Russian character, and Russian cities. The data obtained helped to identify and confirm certain historical patterns and stereotypes concerning the perception of the Russian character. The analysis of the poll results showed that Chinese people’s perceptions of Russia depend largely on their personal experience with Russians. The Chinese who have not been to Russia have an image of our country closely associated with that of the Soviet Union; they have a vague idea of contemporary life in Russia but are quite familiar with the works of Russian classics writers and composers. The Chinese permanent residents of the Russian Federation are more aware of both the classical and contemporary culture of the Russians. In addition, the personality of Russian President Vladimir Putin plays an important role in shaping the current perception of Russia in China. Putin's personality plays an important role in shaping the current perception of Russia.